ON THE ACHARYA INDEX WITH RESPECT TO D-DISTANCE (International Journal of Food and Nutritional Sciences, 2022)
We define Acharya Index AIλ(G) of a connected graph with respect to D-distance as thesum of the D-distance between all pair of vertices of degree d, which is inspired by research on theAcharya index of connected graphs, its chemical implications, and its mathematical traits. In this study, wecalculated the AI(G) for standard graphs.